2014
DOI: 10.1002/erv.2328
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal and Postnatal Psychopathology Among Women with Current and Past Eating Disorders: Longitudinal Patterns

Abstract: This study aims to investigate longitudinal patterns of psychopathology during the antenatal and postnatal periods among women with current (C-ED) and past (P-ED) eating disorders. Women were recruited to a prospective longitudinal study: C-ED (n = 31), P-ED (n = 29) and healthy control (HC; n = 57). Anxiety, depression and ED symptoms were measured at four time points: first/second trimester, third trimester, 8 weeks and 6 months postpartum. Linear mixed effects models were used to test for group differences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 34 publications
2
69
1
1
Order By: Relevance
“…During early pregnancy, 7.5% of women have been reported to have an eating disorder (ED) (Easter et al, 2013), and, despite some reductions women with ED continue to experience high levels of psychopathology throughout the perinatal period (Easter et al, 2014). Maternal ED have been associated with an increased risk of pregnancy and obstetric complications, in particular increased risk of miscarriage, intrauterine growth restriction and low birth weight (Micali et al, 2007;Solmi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During early pregnancy, 7.5% of women have been reported to have an eating disorder (ED) (Easter et al, 2013), and, despite some reductions women with ED continue to experience high levels of psychopathology throughout the perinatal period (Easter et al, 2014). Maternal ED have been associated with an increased risk of pregnancy and obstetric complications, in particular increased risk of miscarriage, intrauterine growth restriction and low birth weight (Micali et al, 2007;Solmi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although ED symptoms are known to decrease during pregnancy (Blais et al ., ; Bulik et al ., ; Crow et al ., ; Lacey, ; Micali, Simonoff, & Treasure, ), recent studies have highlighted how ED cognitions and behaviours persist throughout the course of pregnancy (Micali, Simonoff, et al ., ) and are associated with higher levels of anxiety and depression (Easter et al ., ; Mazzeo, Zucker, Gerke, Mitchell, & Bulik, ; Micali, Treasure, & Simonoff, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies combining eating disorders (AN, BN, and BED) into one group have found between 29 and 78% of women with eating disorders report remission of symptoms during pregnancy with decreased weight and shape concern, restrictive eating, binging, and purging …”
Section: Resultsmentioning
confidence: 99%